Environmental Stress Responses and Experimental Handling Artifacts of a Model Organism, the Copepod Acartia tonsa (Dana) - Nilsson, Birgitte; Jepsen, Per M.; Bucklin, Ann; Hansen, Benni W. (Frontiers in Marine Science, 2018)
Handling animals during experiments potentially affects the differential expression of genes chosen as biomarkers of sub-lethal stress. RNA sequencing was used to examine whole-transcriptome responses caused by laboratory handling of the calanoid copepod, Acartia tonsa. Salinity shock (S=35 to S=5) was used as positive stress control; individuals not exposed to handling or other stressors served as negative stress control. All copepods were grown from eggs to adults without being handled or exposed to any stressors prior the experiment. Survival of nauplii and adults was estimated for up to 10 min of exposure to handling stress and salinity shock. Only adults exhibited decreased survival (44±7% with 10 min of exposure) in response to handling stress and were selected for definitive experiments for RNA sequencing. After 10 min of experimental exposures to handling stress or salinity shock, adults were incubated for 15 min or 24 h at normal culture conditions. A small number of significantly differentially expressed genes (DEGs) were observed 15 min after exposure to handling stress (2 DEGs) or salinity shock (7 DEGs). However, 24 h after exposure, handling stress resulted in 276 DEGs and salinity shock resulted in 573 DEGs, of which 174 DEGs were overlapping between the treatments. Among the DEGs observed 24 h after exposure to handling stress or salinity shock, some commonly-used stress biomarkers appeared at low levels. This suggests that a stress-response was induced at the transcriptional level for these genes between 15 min and 24 h following exposure. Since handling stress clearly affects transcriptional patterns, it is important to consider handling when designing experiments, by either including additional controls or avoiding focus on impacted genes. Not considering handling in gene expression studies can lead to inaccurate conclusions. The present study provides a baseline for studying handling stress in future studies using this model organism and others.